M-All, Trends and Opportunities of Digital Mobility - Roman Coy, David (2012)
The incorporation of mobile technologies has led to a change of habits in the population at all levels, but to date few authors have worked focused on the technological characteristics of mobile devices and consumers, without identifying research in the field of individuals, societies or health. This is the main argument of M-Todos, which brings together the contributions that are being made in the mobile society in both Brazil and Spain.